Effects of Environmental Fe Concentrations on Formation and Evolution of Allophane in Al‐Si‐Fe Systems: Implications for Both Earth and Mars. Issue 12 (4th December 2020) - Du, Peixin; Yuan, Peng; Liu, Jiacheng; Yang, Yixuan; Bu, Hongling; Wang, Shun; Zhou, Junming; Song, Hongzhe; Liu, Dong; Michalski, Joseph R.; Liu, Chengshuai
Abstract: Allophane, a common component on Earth and a probable constituent of the amorphous component on Mars, is closely associated with Fe in the form of structural Fe and/or iron (oxyhydr)oxide coatings. However, until now, the formation and evolution of allophane as products of environmental Fe concentrations have rarely been studied. We investigated allophane precipitation from gels with different Fe/(Fe + Al) molar ratios ( n, 0 ≤  n  ≤ 1.0). X‐ray diffraction patterns and Fourier transform infrared spectra of the products showed that allophane was nearly the only product at n  ≤ 0.2 and that the crystallinity of Fe‐rich allophane decreased with increasing n . Combined with the results of transmission electron microscopy and Mössbauer spectroscopy, Fe was found to be mainly incorporated into the gibbsite‐like sheet of allophane, forming clusters; the highest Fe‐for‐Al substitution content was roughly estimated to be 20 mol.%. As n increased further, the formation of allophane was increasingly suppressed, and the Fe phases began to separate from the Al‐Si phases, resulting in mixtures of incipient allophane and incipient akaganeite and finally akaganeite. The near‐infrared spectroscopic data (1.2–2.6  μ m) of the products showed incapability in identifying poorly ordered minerals in Al‐Si‐Fe systems, while the features in the range of 0.4–1.2  μ m were powerful for studying iron occurrence in the products. These findings not only offer insights into the formation, evolution and geological role of allophane in Al‐Si‐Fe systems on Earth but also help constrain the paleoenvironment of locations where allophane and akaganeite co‐occur on Mars. Key Points: Environmental Fe concentrations control the formation and evolution of allophane in Al‐Si‐Fe systems Near‐infrared spectra (1.2–2.6  μ m) show incapability in identifying short‐range ordered minerals in Al‐Si‐Fe systems Co‐occurrence of allophane and akaganeite would constrain the local palaeoenvironment on Mars